Gabapentin Monotherapy for Refractory Seizures - J Gordon Millichap (Pediatric Neurology Briefs)
The results of an 8-day, controlled, multicenter study of gabapentin monotherapy in 82 hospitalized patients with refractory complex partial or secondarily generalized seizures are reported by members of the US Gabapentin Study Group.